2011
DOI: 10.1111/j.1540-5982.2011.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of unemployment in Canada, 1976–2008

Abstract: This paper studies the flows into and out of unemployment in Canada at an aggregate and a number of disaggregated levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…This increase in the rate at which the unemployed find jobs is equivalent to a decrease in unemployment duration, which is also seen in Macklem and Barillas (). However, as noted in Campolieti (), the reasons for this increase in the job‐finding rate from unemployment are unclear.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This increase in the rate at which the unemployed find jobs is equivalent to a decrease in unemployment duration, which is also seen in Macklem and Barillas (). However, as noted in Campolieti (), the reasons for this increase in the job‐finding rate from unemployment are unclear.…”
Section: Resultsmentioning
confidence: 94%
“…Campolieti () noted that there is a spike in the separation hazard around 1997 and examined some other data sources for similar patterns. Campolieti () concluded that the spike in the separation hazard was most likely related to a change in the wording of the temporary layoff question that was phased in between September 1996 and January 1997 (Sunter et al ., ) that would classify more individuals as unemployed in the Canadian Labour Force Survey that occurred around this time, since the spike is not present in other data. Campolieti () also observed an increase in the Canadian job‐finding hazard around 1997.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, Brochu (2009) finds that job stability rose in Canada between the late 1980s and the mid 1990s and remained stable until 2007. Gray and Finnie (2009) combine data from the Longitudinal Administrative Databank (LAD) and the Status Vector and Record of Employment File of Human Resources and Skills Development Canada to document the receipt of income by particular income source between four years before displacement and five years after displacement for workers aged 45 to 64 who were laid off between 1996and 2002. Campolieti (2011 uses LFS data and examines flows into and out of unemployment over the period .…”
Section: Introductionmentioning
confidence: 99%
“… Unlike the United States, Canada did not have a recession in 2001 (Campolieti 2011), and the recession following the financial crisis that began in the fourth quarter of 2008 was not as severe as the U.S. Great Recession (Campolieti 2012; Cross 2011). …”
mentioning
confidence: 99%